Engaging Rural Youth: The Role of Young People in Integrated Farming Development in Nglanggeran, Gunungkidul Regency - Yayan Restyandi; Yuhan Farah Maulida; Soeharsono Soeharsono; Ratih Ineke Wati (Agro Ekonomi, 2023)
Integrated farming is a farming system with integration patterns in cultivation, livestock, and fisheries. This study aims to examine the role of youth and its effect to integrated farming development in Nglanggeran, Gunungkidul Regency. This research is a quantitative descriptive study. The total number of respondents in this study is 36 farmers selected with simple random sampling. Data collection techniques are observation, documentation, literature review, and in-depth interview. The data analysis uses the proportion test and the multiple linear regression test. The results show that more than 50% of the farmers said that youth played a major role in integrated farming activities. The average level of youth role is 64.33%. Moreover, the role of youth as an agent of change plays a significant role in integrated farming development in Nglanggeran. The influence of an agent of change is positive, which means that the higher the level of the agent of change, the greater the development of the integrated farming. However, the role of youth as an agent of development and an agent of modernization has no significant impact on integrated farming development in Nglanggeran. We conclude that the development of integrated farming in Nglanggeran could increase by engaging the rural youth since they have an important role as an agent of change, an agent of development, and an agent of modernization.